The Use of Misis-Prety Application (Mindfulness Spiritual of Islam for Prenatal Anxiety) Toward Childbirth Anxiety in Covid-19 Pandemic - Tiyara Safitri; Sri Sumarni; Aris Santjaka (Eduvest - Journal of Universal Studies, 2021)
Background: Reports show the prenatal anxiety of Indonesia reaches a percentage of 28.7% of mothers experience anxiety. The COVID-19 pandemic influences pregnant mothers’ psychology, 76.2%. The physical, psychological, and spiritual balance of pregnant mothers should be healthily balanced.  This healthy balance includes the childbirth process to avoid psychological interruption. The use of android application information for obstetric service could improve maternal quality by providing intervention autonomously. Method: This Research & Development used True Experimental Pre and Post-test with Control Group Design. The intervention was with MiSIs-PreTy application to lose the anxiety of primipara pregnant mothers with Trimester III status on the experimental group for 7 days. Every day, the mothers received 30 minutes of implementation. The positive control group, on the other hand, received health education about childbirth preparation. The researchers took 30 respondents as the samples randomly. The data analysis was tested with non-parametric Wilcoxon and Mann Whitney tests. Results: The experts’ validation about the developed application reliability obtained an average score of 92.80% from six aspects. They were based on the ISO 9126 software’s quality, such as usability, reliability, functionality, efficiency, maintainability, and portability. The experiment used the given intervention for both groups. It was effective to lose the anxiety. The effectiveness for experimental group was p < 0.001 while control group obtained p < 0.005. However, the use of the developed application was more effective to lose the anxiety with an average score of 11,8±5,414 for the experimental group than the positive control group with 4,46±4,24. Conclusion: The developed application, MiSIs-PreTy, was validated and revised to be more effective to lose the anxiety of pregnant mothers. Further researches could develop the findings by adding some variables, such as childbirth self-efficacy as the valid measuring tool to examine the pregnant mothers' belief to give birth.